1999
DOI: 10.1023/a:1008365714942
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid increases cytosine arabinoside cytotoxicity in HL-60 human leukemia cells in spite of decreased cellular ara-CTP accumulation

Abstract: At therapeutically relevant concentrations ATRA increased ara-C cytotoxicity and ara-C induced apoptosis but this augmentation is not the corollary of elevated ara-CTP levels. The feasibility of ara-C treatment optimisation via strategies other than those involving elevation of ara-CTP levels should be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The cells were then treated with AraC, a DNA-damaging agent with IC 50 value between 5 and 10M in leukemic cells. 35 To monitor for AraC-induced onset of apoptosis, we measured the cleavage of caspase-7 (C-7) and poly(ADP-ribose) polymerase (PARP) as indicators for their activation and onset of apoptosis. In NB4 cells transfected with empty vector, thus only expressing endogenous level of GRP78, we observed an increase in the level of cleaved C-7 and PARP in an AraC-dosagedependent manner ( Figure 6A).…”
Section: Knockdown Of Grp78 In Human Leukemic Cells Enhances Arac-indmentioning
confidence: 99%
“…The cells were then treated with AraC, a DNA-damaging agent with IC 50 value between 5 and 10M in leukemic cells. 35 To monitor for AraC-induced onset of apoptosis, we measured the cleavage of caspase-7 (C-7) and poly(ADP-ribose) polymerase (PARP) as indicators for their activation and onset of apoptosis. In NB4 cells transfected with empty vector, thus only expressing endogenous level of GRP78, we observed an increase in the level of cleaved C-7 and PARP in an AraC-dosagedependent manner ( Figure 6A).…”
Section: Knockdown Of Grp78 In Human Leukemic Cells Enhances Arac-indmentioning
confidence: 99%
“…The authors showed that ATRA induces transient increases in a CNT-type activity that is not yet well characterized but is presumably associated with a polymorphic variant of known CNTs (17). Moreover, ATRA treatment has been shown to increase ara-C transport and ara-C-induced apoptosis (18,19).…”
mentioning
confidence: 99%
“…To get new insights into the mechanisms underlying resistance/susceptibility of AML cells to cytarabine and doxorubicin, human AML cells derived from patients diagnosed with FAB M2 (HL-60 cell line) and FAB M6 - erythroleukemia (KG-1 cell line) were exposed to these chemotherapeutic agents for 18 h, 24 h and 48 h. Two concentrations of cytarabine were used: 10 μM, the most commonly used cytarabine concentration for human AML cell lines in in vitro assays [ 43 - 45 ] and 1000 μM, to mimic chemotherapeutic regimens consisting of high cytarabine concentrations [ 46 , 47 ]. Regarding doxorubicin, the half maximal inhibitory concentrations (IC 50 ) were used (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%